Introduction: Nice Surprises - Barron, Bruce (2022)
The article presents the discussion on receiving world-class contributions from World Evangelical Alliance. Topics include Dennis Petri heading the International Institute for Religious Freedom and Andrew Messmer, a prolific scholar producing first-ever Spanish-language; and WEA book published in honor of Manfred Kohl, an incredibly transformative and widely loved leader in global theological education.
Keywords: Freedom Of Religion; KOHL, Manfred; PETRI, Dennis; Theological Education; WORLD Evangelical Alliance (Organization)